Perjanjian Hudaibiyah Sebagai Model Kepatuhan Terhadap Perjanjian Internasional dalam Perspektif Islam - Ahmadi, Sidiq (Jurnal Hubungan Internasional, 2015)
This research aims to explain why the Prophet Muhammad comply withThe Hudaybiya Treaty although in its articles are considered harmful. By answering the question above, it is expected to build a model of compliance to international agreement in the Islamic perspective. Christian Reus-Smit’sintertistial conception of politics considered appropriate in this study because it provides space for the role of ideas such as identity and norm in explaining a political action. This study found Prophet Muhammad complieswith Treaty of Hudaibiyah because of political deliberation which integrate four type or reason: idiographic, purposive, ethical, and instrumental. Ideographic deliberation determines the formulation of interest (purposive deliberation). The formulation of these interests will determine the action (instrumental deliberation) in accordance with the available resources and external constrain faced, as well as appropriate with or not contrary to Islamic norms and universally applicable norms (ethical deliberation). Ideographically, based on identities: as believers who should obey Allah and His Messenger, as a noble people who hold the promise. Purposively, the mission of Muslims is to preach the religion of monotheism to all mankind, therefore the condition of peace and religious freedom must be realized. Ethically, the question of how should we act is answered by everything done must in concordance with Islamic rules and customary law norms which emphasize the obligation to comply with the concluded agreements. Instrumentally, the chosen action which in line with the formulated interest and in accordance with the norms of Islam is complieswith the peace treaty.